Islam, Media, dan Identitas Kewarganegaraan : Studi terhadap Representasi Muslim di Media Massa - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Anisa Fajri Azizah; Sri Wahyuni; Melina Arum Dwi Cahyanti (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Mass media plays a crucial role in shaping public perceptions of various groups, including Muslims. This study examines how Muslims are represented in the media and its impact on national identity. The research employs a literature review method with content analysis from academic journals, books, and news reports. The findings show that Muslim representation in the media varies, often exhibiting biases that influence public perception. In politics, Muslims are frequently associated with extremism, particularly in Western media. In social and cultural aspects, negative stereotypes persist despite some media highlighting positive Muslim contributions. These representations impact national identity, either strengthening or weakening individuals' sense of belonging to their country and their access to citizenship rights. Therefore, more objective and balanced journalism practices are needed to support the creation of an inclusive and harmonious society.